The effectiveness of applying different permissible exposure limits in preserving hearing threshold level among automobile industry workers: An intervention study / Balachandar a/l S. Sayapathi - Sayapathi, S.Balachandar (2014)

(untitled)
Introduction The occurrence of occupational noise-induced hearing loss has doubled from 120 million to 250 million in a decade. Countries such as Malaysia, India and the US are adopting 90 dBA as the permissible exposure limit. The aim of this study was to assess the effectiveness of applying 85 and 90 dBA in preserving hearing thresholds and preventing the development of temporary threshold shifts. Methodology In this intervention study, 203 participants from two factories in an automobile industry were exposed to noise levels above the action level of 85 dBA in Factory 1 and 80 dBA in Factory 2, where the permissible exposure limits were 90 and 85 dBA, respectively. The exchange rate of 5-dB was used in both study locations. Noise levels were measured using personal exposure noise dosimeters and a sound level meter. The hearing threshold levels were measured at baseline and then followed up at the first month (post-shift exposure) and again, at the sixth month (pre-shift exposure). Data on hearing threshold levels were measured using a manual audiometer. Hearing protection devices with appropriate noise reduction rate were used to reduce noise exposure among participants. The data analysis was carried out using SPSS version 20.0 for Windows. Data for participants were then imputed as per-protocol analysis and based on the intention-to-treat principle. Independent t-tests, Chi-square tests, Fisher’s exact tests, McNemar’s and repeated measures ANOVA were used in the statistical analysis. iv Results As per-protocol analysis, mean hearing threshold levels on right ear of participants at 3000 and 4000 Hz were statistically significantly lower in Factory 2 with exposure limit at 85 dBA compared to Factory 1 at 90 dBA, (3.17; 95% CI, 0.04-6.30 dBA, p = 0.048, partial η2 = 0.045) and (4.45; 95% CI, 0.05-8.84 dBA, p = 0.047, partial η2 = 0.045), respectively at the sixth month. At the first month analysis, hearing threshold levels of more than 25 dBA of the right ear at 3000 Hz was significantly higher among participants in Factory 1, as per-protocol analysis, χ² (1) = 5.25, φ = 0.203, p = 0.022 (moderate association), and also at the sixth month, at 4000 Hz (right ear), with a continuing level of deterioration; χ² (1) = 4.73, φ = 0.232, p = 0.030 (moderate association). According to the National Institute of Occupational Safety and Health recommended standard, the standard threshold shifts on left ear of participants at 1000 Hz was markedly lower in Factory 2 at the sixth month, as per-protocol analysis, χ² (1) = 3.93, φ = 0.211, p = 0.047 (moderate association). There were no differences in mean scores of knowledge, belief, feeling, judgment and practice domains between participants from the two factories. Conclusion The adoption of 85 dBA as a permissible exposure limit has preserved the hearing threshold among participants compared to those who embraced the 90 dBA. Countries adopting 90 dBA as the permissible exposure limit should review their policy, as the limit adoption of 85 dBA may lower the risk of noise-induced hearing loss. Key Words: Effects 85 or 90dBA; Noise; Threshold shift